Predictors of Posttraumatic Stress Symptoms Among Adolescent and Young Adult Survivors of Childhood Cancer: Importance of Monitoring Survivors' Experiences of Family Functioning. (November 2015) - Kamibeppu, Kiyoko; Murayama, Shiho; Ozono, Shuichi; Sakamoto, Naoko; Iwai, Tsuyako; Asami, Keiko; Maeda, Naoko; Inada, Hiroko; Kakee, Naoko; Okamura, Jun; Horibe, Keizo; Ishida, Yasushi
The purpose of this study was to identify factors associated with posttraumatic stress symptoms (PTSS) among Japanese long-term childhood cancer survivors (CCSs). Subjects comprised 185 adolescent and young adult (AYA) CCSs who completed anonymous self-report questionnaires. Attending physicians also completed an anonymous disease/treatment data sheet. Mean age of survivors was approximately 8 years at diagnosis and 23 years at participation. Multiple regression analysis showed that family functioning, satisfaction with social support, being female, and interactions between family functioning and gender and age at the time of diagnosis were associated with PTSS among survivors. This study revealed family functioning as the most predictive factor of PTSS among AYA CCSs in Japan. Even when the survivor may have unchangeable risk factors, family functioning can potentially moderate the effects on PTSS. Thus, it is crucial for health professionals to carefully monitor and attend to survivors' experiences of family functioning to mitigate PTSS.